1965
DOI: 10.1002/cne.901250303
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of optic fibers in the cat

Abstract: This study undertook to investigate pathways and connections of optic tract fibers in the pulvinar, hypothalamus, ventral lateral geniculate, pretectal region and superior colliculus.Thirty-five adult cats were utilized -28 experimental subjects and seven controls. The right eye was removed and the cats allowed to survive for periods from three to 61 days. The chief method of investigation was the silver impregnation technique of Nauta-Gygax ('54), supplemented by Marchi and luxol-blue cresyl-fastviolet method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1967
1967
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This system is totally contra lateral in many mammals, such as cats, hedgehogs, tree shrews, and red belly squirrels [Meikle and Sprague, 1964;Singleton and Peele, 1965;Campbell et al, 1967;Wu and Shen. 1988], but is partly bilateral in Formosan monkeys [Chen et al, 1987], This system has not been found in echo-locating bats, although it exists in nonecho-locating bats [Simpson, 1984, for review].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system is totally contra lateral in many mammals, such as cats, hedgehogs, tree shrews, and red belly squirrels [Meikle and Sprague, 1964;Singleton and Peele, 1965;Campbell et al, 1967;Wu and Shen. 1988], but is partly bilateral in Formosan monkeys [Chen et al, 1987], This system has not been found in echo-locating bats, although it exists in nonecho-locating bats [Simpson, 1984, for review].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of a number of mammals have shown a common pattern of retinal projections to several subcortical areas, the suprachiasmatic nucleus (SCN), dorsal and ventral lateral geniculate nuclei (dLGN and vLGN), pretectal complex (PRT), supe rior colliculus (SC), pulvinar nucleus, and the ac cessory optic system [Meikle and Sprague, 1964;Singleton and Peele, 1965;Campbell et al, 1967;Glickstein, 1967;Campbell, 1969;Cummings and De Lahunta, 1969;Lund et al, 1974;Takahashi, et al, 1977;Rodieck, 1979;Simpson, 1984;Cooper, 1986;Chen et al, 1987;Cooper and Magnin, 1987], the vis ual system of pangolins has not been examined. The aim of this study, therefore, was to gain data on the visual system in this group by investigating the retinal projections of Chinese pangolins (Manis pentadac tyla) by autoradiography.…”
Section: Introductionmentioning
confidence: 99%
“…Since the PN does not receive a direct input from the optic tract [2,25,37,44,59], the topographical organisation of its visual field representation must be impressed upon it by the nucleus of origin of its afferent fibres. Both neuroanatomical [2,56,66] and physiological [8,10,67] methods have demonstrated a significant input from the dorsal lateral geniculate nucle us to the PN, but without distinguishing between the MIN and the lami nated component of the LGNd as the possible source of the input; only Barris et al [4] have obtained negative results with respect to an intrathalamic connection between LGNd and PN.…”
Section: Projection From Pn To Ipsilateral Occipito-parietal Cortexmentioning
confidence: 99%
“…It is thus important that the pattern of retinal projections to the dorsal and ventral lateral geniculate nuclei we have described for the hedgehog is similar to that described in another species of hedgehog [Campbell, J ane and Y ashon, 1967] as well as to those described in a large number of other mammals including the opossum [Bodian, 1937;G iolli. 1965], phalanger [Packer, 1942;H aymow, 1967], rat [H ayhow , Sefton and Webb, 1962], cat [H ayhow, 1958;Singleton and Peele, 1965;L aties and Sprague, 1969], squirrel [A planalp, 1968; T igges, 1969], tree shrew [T igges, 1966;C ampbell, J ane and Yashon, 1967;A planalp, 1968], rabbit [G iolli and G u thrie, 1969], and monkey [Jones, 1966;Campos-O rtega and G lees, 1967], Although reptiles have been less in tensively studied, the retinal pattern described here for Pseudemys scripla is similar to those described in other species of turtle [Knapp and Kang, 1968 a, b]. These pathways are also similar to those described for the pi geon [Karten and R evzin, 1966].…”
Section: Figmentioning
confidence: 99%